Social Media Utilization of Microbusinesses in A Component City in Northern Philippines - Audrei Ceazar E. Binuluan; Sherry Joy D. Gonayon; Aleya Mae R. Mabborang; Ma. Ruiza C. Panaligan; Khamylle Cate C. Sia; Rizza V. Ramos; Karen Joy A. Catacutan (International Journal of Marketing and Digital Creative, 2024)
Social media has become an essential marketing and communication tool for businesses of all sizes, offering opportunities to engage with customers and promote products in a cost-effective manner. This study explored the use of social media by microbusinesses in a component city in the Northern Philippines, focusing on the platforms used, reasons for adoption, benefits gained, and challenges encountered. A qualitative approach was employed, and 30 microbusiness owners from the service, merchandizing, and manufacturing sectors were selected through quota sampling. Data were collected using an interview guide and analyzed using Braun and Clarke’s Thematic Analysis. The results show that Facebook was the most widely used platform, followed by Instagram and TikTok. The primary reason for using social media was to promote products and services. Benefits include wider market reach, increased sales, and improved communication. However, challenges such as market competition and time management difficulties were identified. Despite these hurdles, social media has proved to be a vital tool for business continuity, particularly during a pandemic. The study highlighted the critical role of social media in supporting the growth and sustainability of microbusinesses and recommended further research to explore other social media platforms and business sizes.